Sexual Orientation Identity Development Milestones Among Lesbian, Gay, Bisexual, and Queer People: A Systematic Review and Meta-Analysis - Hall, William J.; Dawes, Hayden C.; Plocek, Nina (Frontiers in Psychology, 2021)
This paper is a systematic review and meta-analysis on sexual orientation identity development milestones among people who are lesbian, gay, bisexual, or another sexual minority identity (LGB+). Common milestones measured in the 30 studies reviewed were becoming aware of queer attractions, questioning one’s sexual orientation, self-identifying as LGB+, coming out to others, engaging in sexual activity, and initiating a romantic relationship. Milestones occurred in different sequences, although attraction was almost always first, often followed by self-identification and/or sexual activity; coming out and initiating a romantic relationship often followed these milestones. Meta-analysis results showed that the mean effect sizes and 95% confidence intervals varied by milestone: attraction [Mage=12.7 (10.1, 15.3)], questioning one’s orientation [Mage=13.2 [12.8, 13.6]), self-identifying [Mage=17.8 (11.6, 24.0)], sexual activity [Mage=18.1 (17.6, 18.6)], coming out [Mage=19.6 (17.2, 22.0)], and romantic relationship [Mage=20.9 (13.2, 28.6)]. Nonetheless, results also showed substantial heterogeneity in the mean effect sizes. Additional meta-analyses showed that milestone timing varied by sex, sexual orientation, race/ethnicity, and birth cohort. Although patterns were found in LGB+ identity development, there was considerable diversity in milestone trajectories.